ANALISIS KEDISIPLINAN MAHASISWA DALAM PEMBELAJARAN DARING PADA PROGRAM STUDI SISTEM INFORMASI UINSU - Idham Tiofandy Hasibuan; Muhammad Irwan Padli Nasution (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study aims to analyze the impact of online learning on student discipline in attending lectures at the Information Systems Study Program, State Islamic University of North Sumatra. The research employed a quantitative descriptive approach with 86 respondents selected through purposive sampling. Data were collected using an online questionnaire with a five-point Likert scale and analyzed descriptively through frequency, percentage, and mean scores. The results indicate that online learning has a positive impact on students’ learning discipline, with an overall mean score of 3.75 categorized as high. The highest discipline aspect was punctuality in submitting assignments, while the lowest was maintaining attention during online classes. These findings suggest that online learning fosters students’ self-discipline and responsibility when supported by effective instructional design and adequate technological infrastructure. However, improving students’ concentration and engagement remains necessary. Therefore, lecturers are encouraged to implement interactive and feedback-oriented strategies to enhance students’ learning discipline in online environments.